COMPREHENSIVE ASSESSMENT OF METABOLIC SYNDROME IN ELDERLY PATIENTS WITH POLYPHARMACY - Andrade, Ana Carolina de Sousa; Arantes, Bruno Conrado Oliveira; Segundo, Odvaldo Lima Lopes; de Almeida, Elessandra Helena Silva; Lucena, Ester Nogueira dos Santos; Martins, Idel de Oliveira; de Oliveira, Giulia Zoratto; Barbosa, Anna Christiny Fernandes; Gomes, Larah Gonçalves; Viana, Kamilla Gabriella Teixeira; Oliveira, Giovana; Marques, Lara Ribeiro; et al. (Seven Editora, 2025)
Metabolic Syndrome (MS) is characterized by multiple metabolic dysfunctions, such as dyslipidemia, obesity, hyperglycemia, hypertension, prothrombotic and proinflammatory states, related to central fat deposition and insulin resistance. In addition, the prevalence of the pathology in the elderly population varies according to sex, age group, environmental factors, ethnicity, etc. ). In some studies, it is possible to relate MS as a risk factor for cognitive deficit, depression and mobility changes, highlighting the need for a global and individual assessment of the elderly. This study is a qualitative literature review. The sciELO and Virtual Health Library (VHL) databases of the Ministry of Health (LILACS, MEDLINE and IBECS) were used, using the following health descriptors from DeCS/MeSH: “POLYMEDICATION”, “AGED” and “METABOLIC SYNDROME” with the connective “AND” and “AND NOT”. The search sample consisted of scientific articles with the following inclusion criteria: published in the last 10 years between 2014 and 2024 in journals addressing the target audience of the study in English, Portuguese and Spanish, totaling a sample of 82 studies. Twenty-nine scientific articles were selected for the composition of the research. Articles that did not meet the inclusion criteria were excluded. Given the increase in population aging observed in Brazil and worldwide, the phenomenon known as “inflammaging” is notable, that is, a higher degree of inflammation in the elderly population. Thus, this component acts as a phenotype of metabolic syndrome closely related to several chronic non-communicable diseases (NCDs) and their risk factors. Some studies establish a positive association between MS and inflammatory markers, such as Interleukin-6 (IL-6) and C-reactive protein (CRP), although there is still no consensus in the literature. In addition to the lack of consensus regarding inflammatory markers, there are different diagnostic criteria and, respectively, different forms of treatment for the syndrome. Therefore, it is concluded that, based on reviews of recent studies, the prevalence of metabolic syndrome was higher in groups of elderly people with multimorbidity and, consequently, presented polypharmacy and several risk factors for cardiovascular diseases. DOI: https://doi.org/10.56238/sevened2025.029-003